Isolation and characterization of pathology in case of massive mortality by photobacterium damselae subsp. Piscicida in rachycentron canadum - Shimada, Marina T. [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Cueva-Quiroz, Victor A. [UNESP]; Filho, Jair R. Engrácia; Mouriño, Jóse L. P.; Claudiano, Gustavo S. [UNESP]; Moraes, Flávio R. [UNESP]; Moraes, Julieta R. E. [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2020)
This study aimed to investigate outbreak with high mortality in cultured juvenile cobia occurred in Southeast Brazil in 2011. Fish displayed retarded growth rates, lethargy, fin ulceration, skin depigmentation, corneal opacity, and physical deformities. Internally, livers were increased in volume and pale in different degrees. Firm whitish nodules were disseminated in the liver, kidney and spleen. A moderate number of parasites identified as Neobenedenia melleni were recovered from the body surface. Microscopically, severe hepatic steatosis and extensive granulomatous lesion were identified in all fish sampled. Microbiological analysis of moribund fish revealed the presence in pure culture of a Gram-negative bacterium identified as Photobacterium damselae subsp. piscicida using biochemical and molecular characteristics. Analysis of the partial 16S rRNA sequences confirmed the results demonstrating high identity (98%). The isolates were sensitive to chloramphenicol and enrofloxacin and resistant to ciprofloxacin, florfenicol, doxycycline hydrochloride, norfloxacin, oxytetracycline, and tetracycline. Chronic pasteurellosis was considered as the main problem in the farm, while hepatic steatosis and parasitic infestation may have contributed to the development of the process.
Isolamento e caracterização da patologia em caso de mortalidade maciça por photobacterium damselae subsp. Piscicida em rachycentron canadum
Keywords: Antibiotic resistance; Cages; Granulomas; Neobenedenia melleni; Pseudotuberculosis